An Integrated Approach to Pressure Ulcer Prevention and Treatment: The Role of Physical Activity, Nutrition, Care and Modern Technologies. - Mól, Piotr; Łabuś, Małgorzata; Krzykawski, Karol; Sieńko, Antoni; Dołęga, Julia; Hudzińska, Patrycja; Zabawa, Bartłomiej; Maciejczyk, Tomasz; Papież, Łukasz Stanisław; Sadowski, Jakub (Journal of Education, Health and Sport, 2025)
Introduction: Pressure ulcers represent a significant healthcare challenge affecting patient outcomes and quality of life. This comprehensive review examines the integrated approach to pressure ulcer prevention and treatment, focusing on physical activity, nutrition, modern wound care technologies, and emerging therapeutic strategies. Materials and Methods: Literature review was conducted using databases such as PubMed, NCBI, and Google Scholar, with search terms including "pressure ulcers", "physical activity", "nutrition", "wound care", "prevention", "modern technologies" State of knowledge: Pressure ulcers develop when sustained pressure exceeds critical capillary pressures (arterial: ~32 mmHg; venous: 8-12 mmHg), leading to tissue ischemia and necrosis. Physical activity demonstrates significant benefits in wound healing through immune modulation, improved circulation, and enhanced tissue regeneration. Nutritional interventions, particularly protein supplementation (24% vs. 14% protein), show improved healing rates. Modern wound care technologies, including specialized dressings and emerging therapies like hyperbaric oxygen and stem cell treatments, demonstrate promising results. Prevention strategies incorporating risk assessment tools, proper positioning techniques, and skin care protocols significantly reduce pressure ulcer incidence. Conclusions: An integrated approach combining physical activity, proper nutrition, and advanced wound care technologies offers the most effective strategy for pressure ulcer prevention and treatment. Novel diagnostic and therapeutic approaches, including electrical impedance analysis and stem cell therapy, show promise for improving outcomes. Further research is needed to validate emerging technologies and establish standardized treatment protocols.